Minions - Coffin, Pierre; Balda, Kyle; Lynch, Brian (Brian Michael), 1973-; Healy, Janet; Meledandri, Chris; Bullock, Sandra; Hamm, Jon, 1971-; Keaton, Michael, 1951-; Janney, Allison; Coogan, Steve; Saunders, Jennifer; Carell, Steve, 1962-; et al. (Universal City, California : Universal Studios Home Entertainment, 2015)
Minions Stuart, Kevin and Bob are recruited by Scarlett Overkill, a super-villain who, alongside her inventor husband Herb, hatches a plot to take over the world.
DVD release of the 2015 motion picture.
Bonus features: deleted scene; Jingle Bells minion style.
Voices: Sandra Bullock, Jon Hamm, Michael Keaton, Allison Janney, Steve Coogan, Jennifer Saunders, Steve Carell, Pierre Coffin ; Geoffrey Rush, narrator.
MPAA Rating: PG; for action and rude humor.
DVD, widescreen, described video; Dolby Digital 2.0 stereo (English), Dolby Digital 5.1 (English); Dolby Digital 5.1 (French, Spanish); NTSC.
In English, French, or Spanish with optional French or Spanish subtitles; English SDH.
Keywords: Supervillians -- Juvenile drama; Good and evil -- Juvenile drama; Voyages and travels -- Juvenile drama; London (England) -- Juvenile drama; Animated films; Comedy films